Implications of the "Online Ojek Jacket" Symbol on the Culture of Solidarity of the Online Ojek Community D.I Yogyakarta - Tisna Pangestu; Casmini; Nurus Sa'adah (International Journal of Sociology of Religion, 2024)
The online motorcycle taxi community in Yogyakarta Province has been recognized by the wider community with a strong culture of solidarity between fellow online drivers, and the culture of solidarity among online motorcycle taxis can be said to be well established until now. Then the results of this study are related to the implications of the online motorcycle taxi jacket symbol on the culture of solidarity of the Yogyakarta online motorcycle taxi community. And the results are as follows (1) The symbol of the online motorcycle taxi jacket gives the meaning that when the jacket has been used by individuals to work on the road, the individual has a strong attitude and sense of solidarity towards fellow online motorcycle taxis who are on the road. (2) The inherited symbol is a symbol of solidarity culture and although maybe one to another is not very familiar but interestingly when they have met on the road the online ojek have an attitude of helping each other (strong empathy) fellow online ojek.